1982
DOI: 10.1021/i300006a006
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of nylon 66 and Kevlar 29 in elevated temperature, elevated humidity, smog, and ozone

Abstract: Accelerated aging of Nylon 66 and Kevlar 29 yarns was carried out in humid air, smog, and ozone to establish aging trends in these environments. Tensile strengths of nylon yarn aged in a humid environment (50% RH at ambient temperature) for six months degraded from 40% at 1 10 O C to 85% at 150 OC. Kevlar yarns in the same test lost from 10% (130 "C) to 32% (170 "C) of their strength. Based on these data, the estimated energy of activation for the nylon degradation is 18 kcal/mol and for the Kevlar degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 1 publication
3
15
0
1
Order By: Relevance
“…A first‐order kinetic analysis of the declining stress‐at‐break values revealed a linear Arrhenius behavior resulting in activation energy of 165 kJ/mol in the temperature range from 95°C to 135°C. For nylon yarns exposed to humid air (10 and 50% RH ) at elevated temperatures (110°C, 130°C, and 150°C), the literature reports approximately 75 kJ/mol . This deviance may result from different stabilizer packages, reinforcing filler materials, specimen surface‐to‐volume ratios, or different environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A first‐order kinetic analysis of the declining stress‐at‐break values revealed a linear Arrhenius behavior resulting in activation energy of 165 kJ/mol in the temperature range from 95°C to 135°C. For nylon yarns exposed to humid air (10 and 50% RH ) at elevated temperatures (110°C, 130°C, and 150°C), the literature reports approximately 75 kJ/mol . This deviance may result from different stabilizer packages, reinforcing filler materials, specimen surface‐to‐volume ratios, or different environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For the early stages of degradation, activation energy of 15 kJ/mol was reported for water exposed PA66 based on infrared spectroscopic data . For mechanical degradation, however, activation energy of about 75 kJ/mol was deduced . For glass fiber‐reinforced polyamide 66 grades, no activation energies are described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous examples of the limitations in particular measurements can be cited. For example, Mead et al (1982) concluded that "infrared examination of aged nylon yarns with various degrees of degradation showed only slight differences for the most severely degraded samples when compared to controls"; the authors found only slight differences in the infrared absorption spectra of samples that had lost as much as 40% in tensile strength. In another situation, because the discoloration of many polymers is often bleached by the same light source that is used to initiate deterioration, Bendaikha and Decker (1984) point out that "discoloration, although an important parameter in testing the light sensitivity of a polymer, may actually reflect quite imperfectly the extent of photodegradation occurring."…”
Section: Sensitivity Of Measurementmentioning
confidence: 99%
“…Both Hudson, et.al, and Jellinek, et.al. carried out experiments at various temperatures and were able to obtain activation energies. Another group of workers (63) were actually concerned with accelerated aging of nylon and Kevlar by smog and ozone, using tensile strength as the physical measure of degradation. It was found that smog seriously degraded the tensile strength, but ozone did not.…”
Section: Ozone and Other Pollutantsmentioning
confidence: 99%